Energy sources from the eggs of the wolf spider Schizocosa malitiosa: Isolation and characterization of lipovitellins - Laino, Aldana (2013)
In oviparous species, proteins and lipids found in the vitellus form the lipoproteins called lipovitellins that are the major source of energy for the development, growth, and survival of the embryo. The energy resources provided by the lipovitellins have not yet been investigated in the Order Araneae. Using the wolf spider Schizocosa malitiosa (Lycosidae) as an experimental model, we identified and characterized the lipovitellins present in the cytosol, focusing on the energetic contribution of those lipoprotein particles in the vitellus. Two lipovitellins (LV) named SmLV1 and SmLV2 were isolated. SmLV1 is a high-density lipoprotein with 67% lipid and 3.6% carbohydrate, and SmLV2 is a very high-density lipoprotein with 9% lipid and 8.8% carbohydrate. Through electrophoresis in native conditions we observed that SmLV1 has a molecular mass of 559 kDa composed of three apolipoproteins of 116, 87, and 42 kDa, respectively. SmLV2 comprised several proteins composed of different proportions of the same subunits (135, 126, 109, and 70 kDa). The principal lipids of these lipovitellins are sphingomyelin + lysophosphatidylcholine, esterified sterols, and phosphatidylcholine. Lipovitellin-free cytosol contains abundant phospatidylcholine and triacylglyceride related to the yolk nuclei (the vitellus organizing center). The principal fatty acids of SmLV1 and SmLV2 are 18:2 n−6, 18:1 n−9, and 16:0. Spectrophotometry detected no pigments in either the lipovitellins or the cytosol. The egg caloric content was 92 cal/g, at proportions of 59.8% protein, 20.1% carbohydrate, and 19.9% lipid. SmLV1 and SmLV2 provided 19.5% and 17.1% of the calories, respectively. Both lipovitellins contribute mainly with proteins (15.8–18%), with the input of carbohydrates and lipids being lower than 1.3%.